PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA MENGGUNAKAN METODE OBSERVASI LAPANGAN DAN MEDIA BERBASIS TEKNOLOGI - Kaini, Kaini (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
The aim of this research is to describe the improvement of the students' ability of writing text news with the field observation method and technology media for students in grade 8 smp n 1 ella hilir melawi recency. This research use descriptive method with classroom action research in 3 cycles. Every cycle consist of planning, acting, observing and reflecting. The result of this research is the applying of field observation with the use of technology media can improve students in grade 8 smp 1 ella hilir melawi regency's writing ability.